Zr-Rich Eudialyte from the Lovozero Peralkaline Massif, Kola Peninsula, Russia - Taras L. Panikorovskii; Julia A. Mikhailova; Yakov A. Pakhomovsky; Ayya V. Bazai; Sergey M. Aksenov; Andrey O. Kalashnikov; Sergey V. Krivovichev (Minerals, 2021)
The Lovozero peralkaline massif (Kola Peninsula, Russia) has several deposits of Zr, Nb, Ta and rare earth elements (REE) associated with eudialyte-group minerals (EGM). Eudialyte from the Alluaiv Mt. often forms zonal grains with central parts enriched in Zr (more than 3 apfu) and marginal zones enriched in REEs. The detailed study of the chemical composition (294 microprobe analyses) of EGMs from the drill cores of the Mt. Alluaiv-Mt. Kedykvyrpakhk deposits reveal more than 70% Zr-enriched samples. Single-crystal X-ray diffraction (XRD) was performed separately for the Zr-rich (4.17 Zr apfu) core and the REE-rich (0.54 REE apfu) marginal zone. It was found that extra Zr incorporates into the octahedral M1A site, where it replaces Ca, leading to the symmetry lowering from R3¯m to R32. We demonstrated that the incorporation of extra Zr into EGMs makes the calculation of the eudialyte formula on the basis of Si + Al + Zr + Ti + Hf + Nb + Ta + W = 29 apfu inappropriate.